WOCAT SLM Approach: “The 4-Wheels Approach for sustainable scaling [Tunisia]” - Frija, Aymen; Idoudi, Zied; Rudiger, Udo (The Global Database on Sustainable Land Management (SLM) of WOCAT, 2023)
The 4-Wheel Approach is built upon knowledge hubs and partnerships. These knowledge hubs encompass physical structures, such as formal and informal training centers. The purpose of these hubs is to disseminate knowledge, potentially through established partnerships with stakeholders. Four categories of stakeholders, also referred to as change-agents, are identified: i) farmers’ groups and various associations, ii) civil society (including non-governmental organizations (NGOs) and the private sector), iii) national public development partners, and iv) lead farmers and extensionists, who play a pivotal role in locally spreading the technology. Consequently, these knowledge hubs will serve to mainstream technical knowledge through intermediary beneficiaries, who in turn facilitate dissemination to the ultimate users, i.e., farmers. Viewing the approach's scaling and knowledge hubs through this lens underscores the necessity of investing in continuous networking. The success of a knowledge hub and its scalability are contingent upon the business model of a technology. An underlying belief is that technologies primarily capable of generating income or reducing workload for farmers or their organizations will be adopted and can be scaled.